Search for high frequency gravitational-wave bursts in the first calendar year of LIGO's fifth science run - Abbott,BP; Abbott,R; Adhikari,R; Ajith,P; Allen,B; Allen,G; Amin,RS; Anderson,SB; Anderson,WG; Arain,MA; Araya,M; Armandula,H; et al. (Physical Review D Particles Fields Gravitation and Cosmology, 2009)
We present an all-sky search for gravitational waves in the frequency range 1 to 6 kHz during the first calendar year of LIGO's fifth science run. This is the first untriggered LIGO burst analysis to be conducted above 3 kHz. We discuss the unique properties of interferometric data in this regime. 161.3 days of triple-coincident data were analyzed. No gravitational events above threshold were observed and a frequentist upper limit of 5.4year-1 on the rate of strong gravitational-wave bursts was placed at a 90% confidence level. Implications for specific theoretical models of gravitational-wave emission are also discussed. © 2009 The American Physical Society.